Collection of hematopoietic CD34 stem cells in rhesus macaques using Spectra Optia. Issue 5 (31st August 2016) - Haynes, Lynn D.; Coonen, Jennifer; Post, Jennifer; Brunner, Kevin; Bloom, Debra; Hematti, Peiman; Kaufman, Dixon B.
Abstract: Background: Nonhuman primates, particularly rhesus macaques, are ideal preclinical large animal models to investigate organ tolerance induction protocols using donor hematopoietic stem cells (HSCs) to induce chimerism. Their relatively small size poses some challenges for the safe and effective collection of peripheral blood HSCs through apheresis procedures. We describe our experiences using the Spectra Optia apheresis unit to successfully obtain HSCs from mobilized peripheral blood of rhesus macaques. Method: Mobilization of peripheral blood HSCs was induced using granulocyte stimulating factor (G‐CSF) and Mozobil. The Spectra Optia unit was used in 18 apheresis procedures in 13 animals (4.9–10 kg). Animal health was carefully monitored during and after the procedure. Changes in peripheral blood cells before, during and after procedure were determined by complete blood count and flow cytometry. Results: The automatic settings of the Spectra Optia unit were applied successfully to the procedures on the rhesus macaque. All animals tolerated the procedure well with no mortality. Mobilization of HSCs were most consistently achieved using 50 μg/kg of G‐CSF for 5 days and a single dose of Mozobil on the 5th day, followed by collection of cells 3 h after Mozobil injection. The final apheresis product contained an average of 23 billion total nucleated cells with 47% granulocytes, 3, 871 million total CD3 cells and 77 million CD34 cells which resulted in an average of 10 million CD34+ cells/kg of donor weight. Conclusion: Apheresis of peripheral blood mobilized HSCs in rhesus macaques using Spectra Optia is a safe and effective procedure.